2018
DOI: 10.1080/21645515.2017.1417711
|View full text |Cite
|
Sign up to set email alerts
|

The role of basophils as innate immune regulatory cells in allergy and immunotherapy

Abstract: Basophils are circulating cells that are associated quite exclusively with allergy response and hypersensitivity reactions but their role in the immune network might be much more intriguing and complex than previously expected. The feasibility of testing their biology in vitro for allergy research and diagnosis, due fundamentally to their quite easy availability in the peripheral blood, made them the major source for assessing allergy in the laboratory assay, when yet many further cells such as mast cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 232 publications
(265 reference statements)
1
23
0
1
Order By: Relevance
“…Additionally, the analyzed NPs did not interfere with phagocytosis activation as the results showed that the percentage of phagocyting granulocytes did not change compared to E. coli control. Granulocytes are part of the innate immune defense that possess the capacity to recognize foreign materials such as nanoparticles [48,49]. As highlighted by the obtained results, no effect of the SF/PEG NPs ± 5-FU on granulocytes was observed, showing that the investigated NPs do not trigger innate immune system activation.…”
Section: Phagocytic Activity Of Granulocytesmentioning
confidence: 67%
“…Additionally, the analyzed NPs did not interfere with phagocytosis activation as the results showed that the percentage of phagocyting granulocytes did not change compared to E. coli control. Granulocytes are part of the innate immune defense that possess the capacity to recognize foreign materials such as nanoparticles [48,49]. As highlighted by the obtained results, no effect of the SF/PEG NPs ± 5-FU on granulocytes was observed, showing that the investigated NPs do not trigger innate immune system activation.…”
Section: Phagocytic Activity Of Granulocytesmentioning
confidence: 67%
“…Basophils form a small proportion (<1%) of leukocytes in the peripheral blood and enter the peripheral tissues only after activation during infection. Once activated, mast cells and basophils degranulate and release different mediators and cytokines, playing a role in defense against parasitic and bacterial infections (75,77,78).…”
Section: Mast Cell and Basophil Activation Testmentioning
confidence: 99%
“…Mast cells are the stromal components of the inflammatory microenvironment and secrete a myriad of protumorigenic and antitumorigenic molecules depending on the environment, the tumor type, or their peritumoral or intratumoral localization (100). Eosinophils and basophils can also have protumorigenic or antitumorigenic roles, depending on their modulatory and regulatory functions to other immune cells in the TME or to their cytotoxic effects against tumor cells (101103). Increasing evidence suggests that neutrophils, mast cells, eosinophils, or basophils can be potential therapeutic targets in different types of tumors (3, 100).…”
Section: Myeloid Subpopulations In the Tumor Microenvironmentmentioning
confidence: 99%